Assessment of land records management practices in Tanzania's District councils - Mogha, Huruma; Dulle, Frankwell; Benard, Ronald (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2025)
Background of the study: Proper land record management requires consideration of practice procedures. However, land record management in registry offices is insufficient. Purpose: This study aimed to assess the effectiveness of land record management practices in land registry offices in district councils in Tanzania. Method: The study targeted 160 land record staff, purposively selected across 19 districts in three regions of Tanzania. Qualitative data were collected using an interview and observation guide, while quantitative data were collected using a self-administered questionnaire in the study area. Findings: The study found that only record creation practices were more effective with a 2.321 mean score, p< 0.05, while the other five practices were not effective owing to several reasons, including the absence of procedures for guiding land record staff on how to manage land records, and the use of outdated filing classification methods. Conclusion: The use of practice procedures in managing land records in registry offices within district councils in Tanzania will contribute to the effectiveness of land record management.